Financial crime in Romania: a community pulse survey - Achim, Monica Violeta; McGee, Robert W. (Springerriefs in Finance, 2023)
This book explores financial crime and corruption in Romanian society based on a community pulse study. It examines the main behavioral patterns of Romanian society in relation to financial crime variables such as tax compliance, tax morale, corruption in public institutions, and money laundering. The authors also investigate how various demographic aspects (e.g., age, gender, region, professional status, education, etc.) are associated with financial crime. The results of the enclosed survey help policy makers consider best practices in financial governance to reduce the level of financial crime in the region.